«Desire for plenitude» and the Limits of Discourse. A Reading of "Hegemony and Socialist Strategy" from the Perspective of Translatability Theory - Garrido Fernández, Anxo (International Gramsci Journal, 2025)
This article aims to develop a confrontation between the post-foundational proposal of Ernesto Laclau and Chantal Mouffe in Hegemony and Socialist Strategy, and the reflections prompted by Gramsci's treatment of the question of metaphor and his development of a theory of translatability. To this end, we defend two theses. Firstly, that the post-Marxist framework constitutes a successful translation of the anti-economicist problematic into the coordinates of a post-structuralist philosophy. Secondly, that the remainder of this translation lies in the post-Marxist framework's incapacity to incorporate Gramsci's theory of translatability, a fact from which the analytical limits of its formalism derive.